Prizadevanja za dvig pravne varnosti v občinah - Lavtar, Roman (Pravni letopis, 2025)
The article examines the measures undertaken by state authorities to strengthen legal cer- tainty within municipalities. It presents the oversight activities carried out by the ministry responsible for local self-government from a nomotechnical perspective, emphasizing key findings and the most frequent errors identified during inspections. The authors also review previous efforts to catalogue municipal legal acts and discuss forthcoming amendments to legislation that are currently under review.
Keywords: državni nadzor občin; legal certainty; local self-government; lokalna samouprava; municipalities; nomo- technics (legislative drafting); nomotehnika; Občine; pravna varnost; state supervision of municipalities